(untitled) (Research, Society and Development, 2023)
Introduction: Cardiovascular diseases represent the main cause of mortality in the world. Proper management of Medical Myocardial Infarction is based on prompt clearance of the injured coronary artery through Coronary Transluminal Angioplasty, ensuring flow in the region, in addition to the reversal and monitoring of its possible arrhythmogenic complications. The European Society of Cardiology in 2018 defined that door-to-balloon time should be <60 min in institutions with hemodynamics. Objective: To identify, through scientific evidence, the applicability of the door-to-balloon time in up to 60 minutes. Methods: This is an integrative literature review study, with systematization based on Galvão’s steps (2008) with schematization of results conducted in accordance with PRISMA. Results: A total of 1,962 studies were verified, with the exclusion of 1,956 after automated filtering according to the inclusion criteria and reading of articles in full, leaving 6 articles included in the study. Conclusion: It was found that it is feasible to apply the door-to-balloon time in less than 60 minutes. However, it is necessary that there are well-structured public policies in the health care network in the countries where they are applied and, above all, well-defined in-hospital protocols to optimize time in patient care.